Restrained Rocking Response of Equipment on Rigid Floors - El-Hossieny, Ahmed M. (My University, 1985)
Equipment can be mounted on rigid floors by placing the equipment freely on the floor without fastening, fixing it tightly to the floor. This study investigates the rocking response of equipment resting freely on rigid floors and also the effect of restrained rocking on the response of partially fixed equipment under seismic excitations.
Equipment which rests freely on rigid floors is simulated as a rigid rectangular block. The overturning of rigid blocks is studied under the effects of three types of base motion, namely, pulsive, critical, and harmonic excitations.
When the effect of pulse shapes on the overturning potential of rigid blocks under pulsive excitations is examined. It is found that the rectangular pulse will require the least peak acceleration for a specified duration. Under critical excitations, it is found that the extent of response amplification depends on the coefficient of restitution and the initial angle of rotation in addition to the peak acceleration of the pulses. TO amplify the motion by a specified ratio, pulses with lower peak acceleration are required for cases of large initial angles and for cases with large values of the coefficient of restitution. Under harmonic excitation, the conditions for steady-state periodic motion is derived. It is also found that as the coefficient of restitution decreases, the system becomes more stable against overturning and can withstand higher accelerations.
Also in this research, the response of partially fixed equipment resting on rigid floors under the effect of harmonic and earthquake excitations is investigated. For systems restrained by non-yielding bolts, it is found that the existence of gaps has the effect of decreasing the deformation of the mounted equipment relative to the base compares to the case of complete fixation. The existence of gaps also decreases the natural frequency of the system. In systems with yielding bolts, the presence of the gaps affects the deformation of the equipment more than is systems with non-yielding bolts. In the latter, the total rocking angle after all stretching takes place is not sensitive to the initial gap size and depends only on the level of excitation.
Based on this study, it is recommended hat equipment systems be allowed to rock on their bases by providing gaps in their anchorage systems. This kind of mounting has the advantage of allowing the equipment to rock with out the rock without the risk of overturning. Also, larger gaps are recommended for higher floor acceleration levels.
Keywords: Civil Engineering; Civil Engineering